KEANEKARAGAMAN JENIS BURUNG DI TAMAN HUTAN RAYA PANCORAN MAS – DEPOK - Fauzia Lestari, Diandra; Lidiawati , Ina; Sasongko, Dwi Agus (Jurnal Nusa Sylva, 2024)
Species richness of birds was influenced by vegetation structure, canopy cover, and the ability of the land to support bird life. Data on bird species diversity is needed as a basis for management planning in the area. As a Conservation area and life support area, the Pancoran Mas Great Forest Park (Taman Hutan Raya) must be supported by various scientific data and information for management purposes. One is the richness of bird species found in the Tahura Pancoran Mas area. This research aims to identify and inventory bird diversity and determine the composition of their habitat vegetation. This activity will be carried out in June - August 2022. Bird data collection uses the transect route method, while habitat data uses the census method. The birds found consisted of 13 species of birds. The diversity index value is 2.178 (medium) and the evenness index is 0.98 (stable). The species of birds identified are insect and fruit eaters, there is only 1 type that eats fish. There are 86 species of trees, with the dominance of each phase being fruit producers. Trees function as providers of food for birds in the form of fruit, insects, and seeds